2017
DOI: 10.3389/fgene.2017.00061
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the NOT Genes or in the Translation Machinery Similarly Display Increased Resistance to Histidine Starvation

Abstract: The NOT genes encode subunits of the conserved Ccr4-Not complex, a global regulator of gene expression, and in particular of mRNA metabolism. They were originally identified in a selection for increased resistance to histidine starvation in the yeast S. cerevisiae. Recent work indicated that the Not5 subunit, ortholog of mammalian CNOT3, determines global translation levels by defining binding of the Ccr4-Not scaffold protein Not1 to ribosomal mRNAs during transcription. This is needed for optimal translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The Ccr4-Not complex has recently been implicated in cotranslational assembly of the regulatory cap of the proteasome (44). Intriguingly, TSR4 was identified in a screen that also identified multiple components of the NOT complex, suggesting a functional link between Tsr4 and the Ccr4-Not complex (45). Alternatively, the limiting levels of Tsr4 in cells and the rate at which it engages with nascent Rps2 may set the level of Rps2.…”
Section: How Does Tsr4 Facilitate Rps2 Expression?mentioning
confidence: 99%
“…The Ccr4-Not complex has recently been implicated in cotranslational assembly of the regulatory cap of the proteasome (44). Intriguingly, TSR4 was identified in a screen that also identified multiple components of the NOT complex, suggesting a functional link between Tsr4 and the Ccr4-Not complex (45). Alternatively, the limiting levels of Tsr4 in cells and the rate at which it engages with nascent Rps2 may set the level of Rps2.…”
Section: How Does Tsr4 Facilitate Rps2 Expression?mentioning
confidence: 99%
“…Multiple studies suggest that deadenylation contributes to PUF-mediated translational repression ( Goldstrohm et al, 2006 ; Kadyrova et al, 2007 ; Van Etten et al, 2012 ; Weidmann et al, 2014 ). CCR4-NOT deadenylation machinery is conserved in evolution from yeast to humans ( Collart et al, 2017 ; Wahle and Winkler, 2013 ). Although deadenylation is required for germline stem cell maintenance in flies, nematodes and mice ( Berthet et al, 2004 ; Fu et al, 2015 ; Joly et al, 2013 ; Nakamura et al, 2004 ; Nousch et al, 2019 ; Shan et al, 2017 ; Suh et al, 2009 ), the contribution of deadenylation to PUF translational repression in vivo is still controversial ( Weidmann et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that mutations in the NOT genes, or their deletion, resulted in aggregation of newly synthesized proteins, and that this was not observed in cells lacking the deadenylase subunits (Halter et al, 2014 ). Moreover, mutations in ribosomal protein genes or in genes encoding ribosome biogenesis factors were identified in the same selection as the NOT genes (see above) (Collart et al, 2017 ) whereas, mutations in CCR4 or in the CAF genes did not pass this selection (Halter et al, 2014 ). These were all hints for functional heterogeneity of the Ccr4‐Not complex and suggestions that the NOT1‐5 genes may have been identified in a selection revealing factors defective in the translation process.…”
Section: Early Evidence For a Role Of Ccr4‐not In ...mentioning
confidence: 99%